Morphological and molecular characterization of a sexually reproducing colony of the booklouse Liposcelis bostrychophila (Psocodea: Liposcelididae) found in Arizona - Yang, Qianqian; Kučerová, Zuzana; Perlman, Steve J; Opit, George P; Mockford, Edward L; Behar, Adi; Robinson, Wyatt E; Stejskal, Václav; Li, Zhihong; Shao, Renfu (Scientific reports, 2015)
The booklouse, Liposcelis bostrychophila, is a worldwide pest of stored products. For decades, only thelytokous parthenogenetic reproduction was documented in L. bostrychophila. Male L. bostrychophila were first found in Hawaii in 2002. In 2009, a sexual strain was found in Arizona. We examined the morphology of both males and females of the Arizona strain and compared the Arizona sexual strain with the Hawaii sexual strain and the parthenogenetic strains of L. bostrychophila. The sexual and parthenogenetic strains show some differences in eye morphology. To examine the relationship between sexual and asexual lineages, we sequenced the mitochondrial 12S and 16S ribosomal RNA genes of males and females from the Arizona strain. Phylogenetic analyses of L. bostrychophila individuals revealed that: 1) the sexually reproducing colony found in Arizona contains two closely related mitochondrial DNA haplotypes--one present in only females and the other in both males and females; and 2) the Arizona sexual strain was most closely related to a parthenogenetic strain in Illinois. We detected Rickettsia in all of the parthenogenetic individuals we checked but not in any Arizona sexual individuals. Further evidence is required to establish whether the presence of Rickettsia is linked to asexual reproduction in Liposcelis.
Keywords: Molecular Sequence Data; Microscopy, Electron, Scanning; Insecta; Parthenogenesis; RNA, Ribosomal, 16S; DNA, Bacterial; Sequence Alignment; mikroskopie elektronová rastrovací; polymerázová řetězová reakce; Polymerase Chain Reaction; Haplotypes; mužské pohlaví; hmyz; Arizona; DNA, Mitochondrial; DNA bakterií; Base Sequence; sekvence nukleotidů; partenogeneze; ženské pohlaví; RNA ribozomální 16S; Rickettsia; zvířata; mitochondriální DNA; fylogeneze; haplotypy; molekulární sekvence - údaje; Female; RNA ribozomální; sekvenční seřazení; Phylogeny; RNA, Ribosomal; Male; Animals